Food Prices and Political Instability - Arezki, Rabah (IMF Working Papers; Working Paper ;, 2011)
We examine the effects that variations in the international food prices have on democracy and intra-state conflict using panel data for over 120 countries during the period 1970-2007. Our main finding is that in Low Income Countries increases in the international food prices lead to a significant deterioration of democratic institutions and a significant increase in the incidence of anti-government demonstrations, riots, and civil conflict. In the High Income Countries variations in the international food prices have no significant effects on democratic institutions and measures of intra-state conflict. Our empirical results point to a significant externality of variations in international food prices on Low Income Countries' social and political stability.